ADAPTING INTERCULTURAL COMMUNICATION FOR MULTICULTURAL CLASSROOMS IN DIGITAL ERA - Fero, David (Jurnal Visi Komunikasi, 2025)
This study aims to understand the role of intercultural communication among students in the digital era in creating effective communication adaptation in multicultural classrooms. Lack of understanding of students towards intercultural communication is often the cause of ineffective communication, even potentially triggering failure in building harmonious interactions. Students today are part of Generation Z, who were born and grew up in an era of very rapid technological development. Therefore, social media should be used as a source of knowledge that supports students in solving various problems while increasing their ability to adapt to new environments. This study uses a qualitative descriptive method, with data collection techniques through interviews and documentation. The results of the study show that the understanding of intercultural communication obtained by students both through the socialization process in class and through the help of social media plays an important role in accelerating them to overcome communication barriers that arise. The process of adaptation to a new culture also takes place faster thanks to the ease of access to information provided by technological developments in the digital era. This study is expected to encourage the development of a curriculum that is more responsive to cultural diversity in multicultural classrooms, as well as integrating technology-based intercultural communication teaching.